The cutaneous manifestations are significantly related to cerebrovascular in a Serbian cohort of patients with Hughes syndrome. (April 2018) - Stojanovich, L; Djokovic, A; Stanisavljevic, N; Zdravkovic, M
Objectives: To investigate a possible relationship between cerebrovascular, such as stroke and transient ischaemic attack, and various cutaneous manifestations (livedo reticularis, skin ulcerations, pseudovasculitis lesions, superficial cutaneous necrosis and digital gangrene) in antiphospholipid syndrome (APS). This report is based on a Serbian cohort of APS patients. Methods: A total of 508 antiphospholipid syndrome APS patients were assessed: 360 with primary (PAPS) and 148 with APS associated with SLE (SAPS). Antiphospholipid antibodies analysis included detection of anti-cardiolipin (IgG/IgM), anti-ß2 glycoprotein I (IgG/IgM) and positive lupus anticoagulant test. Results: The prevalence of cutaneous manifestations in our cohort was significantly higher in the SAPS group (76.4% vs . 27.2%, p = 0.0001). In both groups, the most common manifestation was livedo reticularis. The majority of cutaneous manifestations were significantly associated with cerebrovascular events in SAPS and PAPS. Cutaneous manifestations were independent predictors of transient ischaemic attack and stroke in PAPS patients (odds ratio 2.850, 95% confidence interval 1.562–5.202, p = 0.001, odds ratio 1.832, 95% confidence interval 1.024–3.277, p = 0.041, respectively). Conclusion: In this cross-section analysis of a large cohort of Serbian APS patients, there was a strong relationship between cutaneous and cerebrovascular manifestations, suggesting a more cautious approach regarding neurological symptoms, especially in PAPS patients with cutaneous manifestations present.